Remote Sensing of Water Quality in Laguna del Sauce, Uruguay - World Bank (World Bank, Washington, DC, 2020)
Laguna del Sauce is a water supply reservoir located in the Department of Maldonado (Uruguay), approximately 15 kilometers west of Punta del Este and 100 kilometers east of Montevideo. This case study assessed ongoing initiatives to address surface water pollution issues in Uruguay, working in partnership with a team of government agencies charged with water resource management. This assessment will contribute to better understanding of options for water-quality remote sensing capabilities and needs. It will also assist the government of Uruguay in identifying appropriate remote sensing tools and devising an application strategy to provide information needed to support decision making regarding the targeting and monitoring of nutrient pollution prevention and mitigation measures.